Spanish comics historical and cultural perspectives - Magnussen, Anne 1964- (Berghahn Books, 2021)
Spanish comics represent an exciting and diverse field, yet one that is often overlooked outside of Spain. Spanish Comics offers an overview on contemporary scholarship on Spanish comics, focusing on a wide range of comics dating from the Francoist dictatorship, 1939-1975; the Political Transition, 1970-1985; and Democratic Spain since the early 1980s including the emergence of the graphic novel in 2000. Touching on themes of memory, gender, regional identities, and history, the chapters in this collection demonstrate the historical and cultural significance of Spanish comics